(untitled) (Bulletin KNOB, 2011)
This article is concerned with two capitals, one from the former convent of Vrouwenklooster, the other from Vrouwenklooster or the nearby monastery of Oostbroek. The small Vrouwenklooster capital dates from around 1139 and its main interest lies in the type of stone that was used, Drachenfels trachyte. At the time this capital was made, this stone was quarried near Heisterbach along the river Rhine by the Cologne cathedral chapter. Its application at Vrouwenklooster may therefore indicate close ties with the bishopric of Cologne. The decoration of the capital is rudimentary and its execution quite sloppy. Consequently, it is likely that the piece was intended for an elevated position. This could have been a bipartite window or opening. The second capital is more interesting from an iconographical point of view, as it is decorated with four grim-looking, grinning monster heads. This capital, too, is likely to have been located in an elevated position. In the article it is argued that the monstrous heads on the capital were not so much intended to ward off danger and demons as is often thought in the literature on such images. Such a function would imply that the monsters were intended as amulets, the use of which was in fact forbidden by the Church. Of course, rules were broken, but as both Vrouwenklooster and Oostbroek were known as strict institutions, the idea that the monster heads were apotropaic in function is out of the question. The idea that such heads represent some sort of social criticism also seems far off the mark. Monsters frequently feature in the monastic literature of the period and were considered to be a scourge, sent to test the religious fervour and stamina of the monastic communities, in much the same way as the biblical figure Job was made to suffer, even though he was a righteous man. One could only truly be considered righteous if one kept one’s faith when faced with affliction. Monsters were thus not to be warded off, for they had a useful task to fulfil. It was the nun’s or monk’s task to stand firm and prove themselves above sin. On the basis of such ideas, it is argued in the article that the monster heads were intended as a message to the demons, that here was an institution where the monks or nuns knew how to deal with evil. They were warriors of Christ and steadfast in their faith. Both pieces indicate that the now lost churches of Vrouwenklooster and Oostbroek must have been representative buildings which - in comparison to ordinary parish churches - were richly decorated. The two capitals thus testify to the once rich monastic culture in the region around Utrecht of which very little has survived.